2009
DOI: 10.4067/s0718-22442009000200003
|View full text |Cite
|
Sign up to set email alerts
|

El Entierro 2 Del Sitio Cañadón Leona 5 (Región De Magallanes, Chile).: Viejos Huesos, Nuevos Datos

Abstract: RESUMENEn este trabajo se presenta el estudio bioarqueológico de los restos óseos humanos del entierro 2 del sitio Cañadón Leona 5 (Región de Magallanes, Chile) excavado por el arqueólogo norteamericano Junius Bird en la década del '30. Se analizaron tanto los procesos fisiológicos y patológicos como las modificaciones tafonómicas que afectaron los ocho individuos (dos subadultos y seis adultos) identificados en el entierro, actualmente depositados en la División de Antropología del Museo Americano de Historia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
(16 reference statements)
1
9
0
2
Order By: Relevance
“…Research into traumatic injuries of large samples associated with violence will be helpful in interpreting the possible paleodemographic changes produced during the Late Holocene and in responses to changes in climate and the availability of resources. Although violent episodes seem to be more common in the continent and in Northern Tierra del Fuego than in Southern Tierra del Fuego, attributed by some authors to population increase (e.g., L'Heureux and Amorosi 2009), the geographical distribution of trauma and its interpretation need more extended study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Research into traumatic injuries of large samples associated with violence will be helpful in interpreting the possible paleodemographic changes produced during the Late Holocene and in responses to changes in climate and the availability of resources. Although violent episodes seem to be more common in the continent and in Northern Tierra del Fuego than in Southern Tierra del Fuego, attributed by some authors to population increase (e.g., L'Heureux and Amorosi 2009), the geographical distribution of trauma and its interpretation need more extended study.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Schinder and Guichón (2003) showed a higher prevalence in individuals with terrestrial (33%) and mixed (20%) diets than in those with marine (2%) diets. L'Heureux and Amorosi (2009) described 43% of the individuals in a sample of nine from the site Cañadón Leona 5 as exhibiting AMTL. In a sample from the postcontact period, García Laborde and others (2010) observed 33.3% of the individuals as exhibiting AMTL.…”
Section: Recent Paleopathological Researchesmentioning
confidence: 99%
“…De acuerdo con las interpretaciones realizadas por diferentes autores, las lesiones antemortem fueron causadas por accidentes o por episodios de violencia interpersonal (Constantinescu 2003;L'Heureux y Amorosi 2009;Underdown 2012). En cambio, todas las lesiones de tipo perimortem fueron relacionadas a heridas por proyectiles líticos en la pelvis y golpes en el cráneo que pudieron ser intencionales, probablemente a través del uso de bolas de boleadoras (Suby y Guichón 2010;Suby et al 2008), lo que indica claros eventos de violencia interpersonal.…”
Section: Interpretación De Lesiones Traumáticas En Patagonia Australunclassified
“…Possibly related to this fact, no cemeteries from prehistorical times were found. The majority of burials in southern Patagonia include only one isolated individual (Guichón, Barberena, & Borrero, 2001;Suby et al, 2017), and only a few of multiple burial from prehistoric times were found (e.g., L'Heureux & Barberena, 2008;L'Heureux & Amorosi, 2009, 2010Santiago et al, 2011). As a consequence, the bioarchaeological record from southern Patagonia is relatively scarce and fragmentary.…”
Section: Ethnographic and Archaeological Backgroundmentioning
confidence: 99%